CAST AWAY, a Membrane-Associated Receptor-Like Kinase, Inhibits Organ Abscission in Arabidopsis(1)([C])([W])([OA]) - Burr, Christian A. (American Society of Plant Biologists, 2011)
Receptor-like kinase-mediated cell signaling pathways play fundamental roles in many aspects of plant growth and development. A pair of Arabidopsis (Arabidopsis thaliana) leucine-rich repeat receptor-like kinases (LRR-RLKs), HAESA (HAE) and HAESA-LIKE2 (HSL2), have been shown to activate the cell separation process that leads to organ abscission. Another pair of LRR-RLKs, EVERSHED (EVR) and SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE1, act as inhibitors of abscission, potentially by modulating HAE/HSL2 activity. Cycling of these RLKs to and from the cell surface may be regulated by NEVERSHED (NEV), a membrane trafficking regulator that is essential for organ abscission. We report here the characterization of CAST AWAY (CST), a receptor-like cytoplasmic kinase that acts as a spatial inhibitor of cell separation. Disruption of CST suppresses the abscission defects of nev mutant flowers and restores the discrete identity of the trans-Golgi network in nev abscission zones. After organ shedding, enlarged abscission zones with obscured boundaries are found in nev cst flowers. We show that CST is a dual-specificity kinase in vitro and that myristoylation at its amino terminus promotes association with the plasma membrane. Using the bimolecular fluorescence complementation assay, we have detected interactions of CST with HAE and EVR at the plasma membrane of Arabidopsis protoplasts and hypothesize that CST negatively regulates cell separation signaling directly and indirectly. A model integrating the potential roles of receptor-like kinase signaling and membrane trafficking during organ separation is presented.